Purification and characterization of kojic acid produced from pineapple waste by aspergillus flavus link 44-1 via solid substrate fermentation (SSF) - Mohammad Syarifuddin, Mohamad Saidi (Universiti Malaysia Sarawak, UNIMAS, 2013)
Kojic acid is an organic acid that is highly demanded in cosmetic, medical, and food industries. The present study was aimed to purify and characterize of kojic acid produced from pineapple waste. Crystallization technique was applied in purifying the kojic acid. Subsequently, characterization was based on NMR, UV and HPLC analyses. The results showed that about 1.5% (w/w) kojic acid could be traced from NMR analysis while the HPLC results indicated the presence of approximately 0.025g/L kojic acid produced from 5 gram of pineapple waste. From this study, it can be suggested that crystallization technique should be enhanced with supplementary procedures in enhancing the quality of kojic acid produced from pineapple waste in future.